2020
DOI: 10.1108/jbim-05-2019-0192
|View full text |Cite
|
Sign up to set email alerts
|

When does coopetition affect price unfairness perception? The roles of market structure and innovation

Abstract: Purpose This study aims to examine the critical role of types of coopetition (upstream/downstream), market structure (concentrated/competitive) and innovation (low vs high degree of innovation) that can affect the way consumers perceive the resulting price (un)fairness of new offerings. Design/methodology/approach Three between-subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 120 publications
1
7
0
Order By: Relevance
“…First, conflicts tend to be related to products and tasks, which can be related to shares of margin and price negotiations as presented by Wilhelm (2018). As prior research has been lacking studies exploring the effects of coopetition on prices fairness (Sabri et al, 2020), our study shows that coopetition increases the knowledge of price fairness of both relationship parties, and in our case study, was found to be one of the issues increasing competitive activities. This is somewhat different in comparison with prior findings of studies of vertical coopetition, showing that perceived fairness is important for the duration of the relationship between the firms (Soppe et al, 2014).…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…First, conflicts tend to be related to products and tasks, which can be related to shares of margin and price negotiations as presented by Wilhelm (2018). As prior research has been lacking studies exploring the effects of coopetition on prices fairness (Sabri et al, 2020), our study shows that coopetition increases the knowledge of price fairness of both relationship parties, and in our case study, was found to be one of the issues increasing competitive activities. This is somewhat different in comparison with prior findings of studies of vertical coopetition, showing that perceived fairness is important for the duration of the relationship between the firms (Soppe et al, 2014).…”
Section: Discussionmentioning
confidence: 49%
“…As far as types of conflicts are concerned, Wilhelm (2018) argues that tensions typical of vertical coopetition are related to the degree of vertical integration and to shares of margins and price negotiations. In addition, price fairness is identified as a critical determinant of customer satisfaction and sales, which are key metrics for measuring coopetition effectiveness (Crick, 2019;Sabri et al, 2020). Our findings show that the nature of conflicts in vertical coopetition varies and develop over time and that episodes of conflict are related to each other.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Based on the AMC perspective and transaction cost theory, our study makes three advances. First, when a focal firm is aware of low requirements and efficiency benefits from joint price elevation, the firm can prevent negative client perceptions of B2B cooperative actions (Sabri et al, 2020). Second, there is low risk to interfirm motivation for cooperative joint actions which decreases environment uncertainty.…”
Section: Jointly Elevating Price and Firm Performancementioning
confidence: 99%